2018
DOI: 10.1111/trf.14575
|View full text |Cite
|
Sign up to set email alerts
|

AutomatedRBCexchange compared to manual exchange transfusion for children with sickle cell disease is cost‐effective and reduces iron overload

Abstract: Erythrocytapheresis reduces iron overload and allows a longer interval between procedures without a higher RBC requirement from the second year on aRBX. The cost did not increase as estimated in our Belgian Health Care System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 52 publications
0
37
1
Order By: Relevance
“…Automated exchange was associated with a lower increase in ferritin than manual exchange as automatic exchange transfusion is an isovolumetric process that can accomplish a larger, more efficient exchange of RBCs. 8,9 Our results are distinctly different from prior single center studies that have demonstrated automatic exchange transfusion limits excessive iron stores [10][11][12][13][14][15] because our primary results did not have to adjust for treatment with or adherence to chelation therapy and intra-individual differences in absorption of chelation. Even when we included those that received some chelation therapy in the first year, there was no significant difference in the primary finding that automated RBC exchange transfusion is associated with a lower rise of ferritin levels when compared to manual exchange or simple blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 76%
“…Automated exchange was associated with a lower increase in ferritin than manual exchange as automatic exchange transfusion is an isovolumetric process that can accomplish a larger, more efficient exchange of RBCs. 8,9 Our results are distinctly different from prior single center studies that have demonstrated automatic exchange transfusion limits excessive iron stores [10][11][12][13][14][15] because our primary results did not have to adjust for treatment with or adherence to chelation therapy and intra-individual differences in absorption of chelation. Even when we included those that received some chelation therapy in the first year, there was no significant difference in the primary finding that automated RBC exchange transfusion is associated with a lower rise of ferritin levels when compared to manual exchange or simple blood transfusion therapy.…”
Section: Discussioncontrasting
confidence: 76%
“…Nine studies compared automated RCE with simple transfusion (average patient ages in the studies, 7.3-20 years), [85][86][87][88][89][90][91][92][93] and 6 studies compared automated RCE with manual RCE (average patient ages in the studies, 5.9-27 years). 87,[94][95][96][97][98] Most patients were of the SS genotype.…”
Section: Remarks: Cmentioning
confidence: 99%
“…Acute and chronic transfusions are sometimes needed in SCA to improve the clinical status of the patients . The replacement of abnormal hemoglobin and sickled RBCs was originally achieved by prophylactic transfusions associated with manual bloodletting, but this methodology did not prevent iron overload . Conversely, RBC exchange (RBCX) using an apheresis device can replace a larger number of RBCs without inducing iron overload .…”
mentioning
confidence: 99%
“…The replacement of abnormal hemoglobin and sickled RBCs was originally achieved by prophylactic transfusions associated with manual bloodletting, but this methodology did not prevent iron overload . Conversely, RBC exchange (RBCX) using an apheresis device can replace a larger number of RBCs without inducing iron overload . Several studies showed its safety and efficiency in preventing the occurrence of SCA complications when regularly performed .…”
mentioning
confidence: 99%
See 1 more Smart Citation